2020
DOI: 10.1248/cpb.c20-00135
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting 2-Alkoxy-3-bromoindolines: Control C-2 <i>vs</i>. C-3 Elimination for Regioselective Synthesis of Alkoxyindoles

Abstract: The regioselective synthesis of both 2-and 3-alkoxyindoles from a common intermediate, 2-alkoxy-3-bromoindolines (ROBIN), is described. The 2-alkoxyindoles are obtained by a base-promoted regioselective elimination of HBr from ROBIN, whereas the synthesis of 3-alkoxyindoles is achieved by a silvermediated alkoxylation followed by an acid-promoted elimination of alkoxide. This key elimination features the complete regioselectivity and no need for catalysts, that makes it have potential synthetic applications. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…168,169 Similar haloetherifications have also been utilised by others in the synthesis of 2-alkoxy-3-bromoindolines and substituted deltacyclenes. 170,171 It has since been shown that, by introducing Brønsted acid catalysts in NXS-mediated haloalkoxylation reactions, times could be reduced and the scope of the reactions increased, all while retaining Markovnikov selectivity. Such halogenation reactions have been demonstrated to be promoted by H 2 SO 4 , 172 NH 4 OAc, 173 thiourea 174 and a more elaborate recyclable polyfluorinated hydrazine 1,2-bis(carbothioate) organocatalyst 175 (Scheme 35).…”
Section: Halogen-mediated Alkene Difunctionalisationmentioning
confidence: 99%
See 1 more Smart Citation
“…168,169 Similar haloetherifications have also been utilised by others in the synthesis of 2-alkoxy-3-bromoindolines and substituted deltacyclenes. 170,171 It has since been shown that, by introducing Brønsted acid catalysts in NXS-mediated haloalkoxylation reactions, times could be reduced and the scope of the reactions increased, all while retaining Markovnikov selectivity. Such halogenation reactions have been demonstrated to be promoted by H 2 SO 4 , 172 NH 4 OAc, 173 thiourea 174 and a more elaborate recyclable polyfluorinated hydrazine 1,2-bis(carbothioate) organocatalyst 175 (Scheme 35).…”
Section: Halogen-mediated Alkene Difunctionalisationmentioning
confidence: 99%
“…168,169 Similar haloetherifications have also been utilised by others in the synthesis of 2-alkoxy-3-bromoindolines and substituted deltacyclenes. 170,171…”
Section: Alkene Difunctionalisationmentioning
confidence: 99%
“…However, these reactions are limited to the construction of either C2-oxygenated or C3-oxygenated indole/indoline. Given the difficulty of switchable construction for oxygenated indole/indoline, we recently reported the regioselective synthesis of both 2-and 3-alkoxyindoles from the common intermediate, 2-alkoxy-3-bromoindolines (ROBIN) [48]. The synthesis of 2-alkoxyindoles was achieved by a base-mediated regioselective elimination of HBr from ROBIN.…”
Section: Introductionmentioning
confidence: 99%
“…In our research program exploiting indolines 13,14 as umpolung indole reagents, 15 we have established 3-azido-2-methoxyindolines (AZINs) as a 3-azidoindole surrogate in the presence of a Lewis acid (Scheme 2a). 16 The resulting 3-azidoindoles undergo ipso -substitutions of the azido group by nucleophiles with a formal loss of azido moieties, affording 3-substituted indoles.…”
Section: Introductionmentioning
confidence: 99%